Cotas para negros em universidades públicas no Brasil: significados da política contemporânea de ação afirmativa - Vieira, Paulo Alberto dos Santos (Universidade Federal de São Carlos, 2012)
This text aims to discuss the current policies concerning affirmative actions, especially the racial cotes, which in 2002 were implemented in Brazilian universities, above all in the public ones. After nearly one decade that the country has more than hundreds of institutions that have adopted these policies (with different emphasis and models), the controversy is not ended. The main controversy arises especially when these affirmative actions focus on aspects related to race in the models implemented in these educational institutions. This thesis is divided in three chapters. We have tried to develop a theoretical line approaching the current debate, which has been attempting to influence people and social groups, as well as politicians, either in favor or against the policies. The chapters are about relevant topics for this research: the construction of the nation and how science and social theories were important to create a society based on social hierarchy related to race. There is also a discussion about the reception of the racial cotes in a public university that applies racial criteria to select students for the graduation courses. Thus, the chapters try to understand how the process of racialization happened in Brazil and how this process was responsible for the creation of inflexible positions in terms of social status. This society is the same which is now discussing questions and themes that tend to appear against that stiff hierarchy. Therefore it is apparently clear that a paradox has been recently placed. The affirmative action‟s policies have always been supported, or at least not firmly criticized. On the other hand, when the same structure of the affirmative action‟s policies is used in favor of black people, it raises negative and opposite reactions. Making an effort to understand this reaction, we, first of all, have the hypothesis that the affirmative action‟s policies, mainly the racial cotes, allow us to establish at least two levels of comprehension: firstly, the emphasis in the process seeking equality; secondly, the proposal of a reflection about the difference – including the ethnic and racial ones. These two last have been one of the central elements of social inequality. Hence, our research challenges to show that the contemporary policies of affirmative action, mostly the racial cotes, cause a tension on the Brazilian social thought spotting other possibilities of interpretation for this society. Consequently, giving conceptual, theoretical and political strengths to the sociological category of race, it has allowed a new understanding for the social phenomenon in the country and a broader comprehension of what are the true elements involved whenever the racial cotes become one of the greatest symbols not only the public symbols not only the public higher education, but also the racial relation in Brazil in our time.
Keywords: Teoria social; Cotas para negros; Ação afirmativa; Universidade; Brasil; Social theory; Racial cotes; Affirmative action; University; Brazil; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL